"The Cabbage is a Rose": Feminist Eco-aesthetics from Surrealism to Contemporary Art - Ferentinou, Victoria ca. 20. Jh. (Approaching religion, 2025)
This essay revisits art as an alternative epistemology that probes the parameters of the real and the complicated entanglements between humans and non-humans from an eco-feminist perspective. It builds upon the work of Leonora Carrington and her deployment of the Surrealist marvellous fuelled by her engagement with occulture and explores, its ecological and feminist implications. It also comments on the multiple responses their legacy has engendered in the contemporary artistic scene, especially by artists such as Emma Talbot, who responds to the current sociopolitical and ecological crisis. The discussion is framed by an eco-feminist reconfiguration of aesthetics as feminist eco-aesthetics that can be used for shedding light on the various discursive strategies at work in artistic practices in which eco-occulture and the gender-political crossover. Premised upon reflections on the artwork by women Surrealists and insights drawn from eco-feminism, eco-criticism, feminist post-humanities and new materialism, feminist eco-aesthetics is defined as a set of radical visual strategies and modes of learning predicated upon multi-species interdependence, symbiotic being and ethics of care. This is a non-dualist aesthetics that offers artists a more efficient strategy to unsettle hierarchical images of the world and touch upon the socio-political oppression of women and of the entire web of interconnected non-human beings.